Lal's remedies of government servatns in service matters under the administrative tribunals act, 1985 (Allahabad, 1990)
The book contains section-wise commentary and has been divided into chapters topic wise, each chapter further has been divided into headings and sub-headings. The various positions of the new venture have been explained in simple and easily understandable language with reference to decided cases under the Act. A copious General Index has also been added in both the volumes. This book is also a veritable boon for all the Legal Practitioners, the Public and other Government servants covered under the Act. A highly useful book not only to the Tribunals, Legal Practitioners, Administrators and Bureaucrats but also to persons aggrieved by any order of the authorities.
Keywords: Administrative law